2021
DOI: 10.1021/acs.orglett.0c03950
|View full text |Cite
|
Sign up to set email alerts
|

Additive-Controlled Divergent Synthesis of Tetrasubstituted 1,3-Enynes and Alkynylated 3H-Pyrrolo[1,2-a]indol-3-ones via Rhodium Catalysis

Abstract: Herein we report the additive-controlled divergent synthesis of tetrasubstituted 1,3-enynes and alkynylated 3Hpyrrolo[1,2-a]indol-3-ones through rhodium-catalyzed C-H alkenylation/DG migration and [3+2] annulation, respectively. This protocol features rare directing group migration in 1,3-diyne-involved C-H activation, excellent regio-and stereoselectivity, excellent monofunctionalization over difunctionalization, broad substrate scope, moderate to high yields, good functional group compatibility and mild redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 134 publications
2
23
0
Order By: Relevance
“…However, directing group‐assisted coupling cyclization of indoles with 1,3‐diyne precursors have remain unexplored. Very recently, a remarkable example by Zhang and co‐workers showed that an Rh(III) catalyzed synthesis of tetrasubstituted 1,3‐enynes and alkylated 3 H ‐pyrrolo[1,2‐ a ]indol‐3‐ones derivatives from indoles and 1,3‐diynes (Scheme 1c) [17] . However, the methodology showed a limited scope of dialkynes and most of the products derived with alkyl substituted 1,3‐diyne precursors.…”
Section: Methodsmentioning
confidence: 99%
“…However, directing group‐assisted coupling cyclization of indoles with 1,3‐diyne precursors have remain unexplored. Very recently, a remarkable example by Zhang and co‐workers showed that an Rh(III) catalyzed synthesis of tetrasubstituted 1,3‐enynes and alkylated 3 H ‐pyrrolo[1,2‐ a ]indol‐3‐ones derivatives from indoles and 1,3‐diynes (Scheme 1c) [17] . However, the methodology showed a limited scope of dialkynes and most of the products derived with alkyl substituted 1,3‐diyne precursors.…”
Section: Methodsmentioning
confidence: 99%
“…The work by Fei Zhao, Xiaowei Wu, and Xiaoning Zhang, and co-workers in 2021 introduced a rhodium-catalyzed redox neutral additive controlled switchable synthesis of tetrasubstituted 1,3-enynes 67 and alkynylated 3H-pyrrolo[1,2-a] indol-3-ones 65 (Scheme 45). 26 High regio-and stereo-selectivity, as well as selective mono-functionalization over di-functionalization, are the notable features of this reaction.…”
Section: Scheme 44 Control Experimentsmentioning
confidence: 99%
“…Moreover, despite the remarkable advantages such as excellent stereoselectivity and high atom‐economy, this method still shows some minor drawbacks such as the usage of excessive additives and the requirement of chromatography for the purification of products. Considering the low cost and outstanding catalytic performance of Ru catalysts in C−H activation, [14] and together with our interests in TM‐catalyzed C−H functionalization [11d–g,12,15] and indole compound synthesis, [16] herein we report an efficient Ru(II)‐catalyzed C−H alkenylation/DG migration cascade between N ‐carbamoyl indoles and alkynes for the regio‐ and stereoselective assembly of tetrasubstituted alkenes carrying the privileged indole substituent (Scheme 2c). Notably, the carbamoyl DG [17] is endowed with a dual role of auxiliary group and internal acylation reagent via C−N bond cleavage, which migrates onto the alkene moiety of the products to deliver tetrasubstituted α,β‐unsaturated amides.…”
Section: Introductionmentioning
confidence: 99%